POSTOPERATIVE ANALGESIA WITH INTRAPERITONEAL ROPIVACAINE WITH AND WITHOUT DEXMEDETOMIDINE AFTER TOTAL LAPAROSCOPIC HYSTERECTOMY: A RANDOMIZED, DOUBLE-BLIND, CONTROLLED TRIAL - Acharya, Ranjita; Karan, Daisy; Khetan, Megha (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: In this advanced era of surgery, laparoscopic hysterectomy operations are very commonly practiced by surgeons. It reduces trauma, morbidity, and health-care costs, ensuring early discharge. However, the early post-operative pain experienced by patients may sometimes negate all the advantages of a laparoscopic procedure. Intraperitoneal (IP) instillation of local anesthetics has been proposed to decrease post-operative pain after laparoscopic surgeries. Additives to local anesthetics like α-2 agonists such as clonidine and dexmedetomidine prolong the duration of analgesia. Therefore, this randomized, prospective, controlled study was conducted to compare the analgesic efficacy of IP ropivacaine with or without dexmedetomidine for postoperative analgesia after total laparoscopy hysterectomy. Methods: At the end of laparoscopic hysterectomy, in a double-blind, randomized manner, one of the following injections was given intraperitoneally. The patients were allocated into the following two groups: The patients in ropivacaine group (R group) (N = 40) were given 38 ml of 0.2% ropivacaine plus 2 ml of normal saline (NS) and the patients in ropivacaine plus dexmedetomidine group (RD group) (N = 40) were given 38 ml of 0.2% ropivacaine combined with 0.5 μg/kg dexmedetomidine (diluted in 2 ml NS) through trocars. All the patients were given diclofenac sodium when they had a pain score of 4 on visual analog scale (VAS). Results: VAS score at different time intervals was significantly lower after the second postoperative hour, time to first request of analgesia (minutes) was longest (487.7±40.96 vs. 242.5±19.84), and the total analgesic consumption (mg) was lowest (61.88±37.55 vs. 183.75±44.78) in RD group than in R group. Conclusion: The antinociceptive effects of the IP instillation of ropivacaine in combination with dexmedetomidine are superior to ropivacaine alone in laparoscopic hysterectomy cases. Keywords: Dexmedetomidine, Ropivacaine, Laparoscopic Hysterectomy.